2022
DOI: 10.31234/osf.io/34ckf
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Woman or tennis player? Visual typicality and lexical frequency affect variation in object naming

Abstract: Speakers often use different names to refer to the same entity (e.g., “woman” vs. “tennis player”). We here explore factors that affect naming variation for visually presented objects. We analyze a large dataset of object names with realistic images and focus on two factors: visual typicality (of both objects and the contexts they appear in) and name frequency. We develop a novel computational approach to estimate visual typicality, using image representations from Computer Vision models. Specifically, we comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…However, there may be a general bias towards the visually more salient object (here the batter in the front), which speakers take into account when choosing their expression. Similar considerations can be made for visual typicality with a bias towards the more typical candidate object for a given name (for an analysis of typicality effects on lexical choices see Gualdoni, Brochhagen, Mädebach, & Boleda, 2022).…”
Section: General Context Effectmentioning
confidence: 95%
“…However, there may be a general bias towards the visually more salient object (here the batter in the front), which speakers take into account when choosing their expression. Similar considerations can be made for visual typicality with a bias towards the more typical candidate object for a given name (for an analysis of typicality effects on lexical choices see Gualdoni, Brochhagen, Mädebach, & Boleda, 2022).…”
Section: General Context Effectmentioning
confidence: 95%
“…Similarly, Graf et al (2016) asked participants to name one of three presented images, which could be of the same or different basic-level or superlevel category, and investigated as their dependent variable the level of description of the produced labels. In very recent studies, Gualdoni and colleagues (Gualdoni et al, 2022(Gualdoni et al, , 2023 examined the ManyNames dataset Silberer, Zarrieß, Westera, & Boleda, 2020), which contains different human-generated image labels for a large set of images -in the vast majority of LEXICAL CHOICE IN A TABOO GAME PARADIGM 5 cases multiple labels with different production frequencies per image. Using computer vision models, Gualdoni and colleagues demonstrated that this naming variation could be predicted from the image typicality (see also ) for these different labels (Gualdoni et al, 2022), and developed a computational measure of label informativeness that predicts the level of description of the produced labels (Gualdoni et al, 2023).…”
Section: Lexical Selection Lexical Choice and Word Formationmentioning
confidence: 99%
“…We operationalized visual similarity using computationally derived visual representations of meanings. We followed a two-step proce-dure, drawing on existing work (15,31). First, we used a computer vision model (32) to produce representations for images of instances of meanings (e.g., for images of dogs for the meaning "dog").…”
Section: Frameworkmentioning
confidence: 99%